Meningkatkan Keterampilan Kerjasama, Dan Hasil Belajar Muatan IPA Tema 6 Menggunakan Kombinasi Model PJBL, GI, Dan NHT Pada Siswa Kelas V SDN Kuin Selatan 1 Banjarmasin - Sifa Noor Anggraini; Amberansyah (Jurnal Pendidikan Sosial Dan Konseling, 2023)
The problems raised from this study are the low activity, student collaboration skills and student learning outcomes. The reason is that students are less involved in learning, lack of interaction between students (student involvement in collaboration), monotonous learning, and students do not understand the learning material. The purpose of this study is to describe teacher activities, analyze student activities, cooperative skills, and student learning outcomes. Class action research (CAR) that was carried out was for 4 meetings. This research was carried out at Kuin Selatan 1 Public Elementary School, Banjarmasin City, in class VB students with a total of 17 students in the 2022/2023 school year. Acquisition of data obtained is quantitative and qualitative data. The results of this study indicate that the teacher's activity in meeting 4 obtained a score of 97%. Student activity at meeting 4 obtained 88%. Student cooperation skills at meeting 4 obtained 94%. Student learning outcomes at meeting 4 reached 94%. Based on these findings it can be concluded that learning using a combination of Project Based Learning, Group Investigation, and Numbered Head Together models can increase student activity, collaboration skills and student learning outcomes.